Lusophone African short stories and poetry after independence : decolonial destinies - Aidoo, Lamonte, 1986-; Aidoo, Lamonte, 1986-; Silva, Daniel F., 1985-; Silva, Daniel F., 1985- (Anthem studies in race, power and society., 2021)
In 1975, after much resistance, Portugal became the last colonial power to relinquish its colonies on the African continent. The tardiness of Portuguese decolonization in Africa (Cabo Verde, Angola, Mozambique, Guinea Bissau, São Tomé e Príncipe) raises critical questions for the emergence of national literary and cultural production in the wake of national independence. Bringing together the works of poets, short story writers, and journalists, this book charts the emergence and evolution of the national literatures of Portugal's former African colonies, from 1975 to the present. The aim of this book is to examine the ways in which writers contended with the process of decolonization, forging national, transnational, and diasporic identities through literature while grappling with the legacies and continuities of racial power structures, colonial systems of representation, and the struggles for political sovereignty and social justice. This book will be the first of its kind in English to include canonical, emerging, and previously untranslated authors of poetry and short-form fiction to a new public.--